Sentiment analysis of Google reviews based on service qual-ity dimensions related to patient satisfaction - Silvie Adistiana Wijaya; Ratna Indrawati (Green Inflation: International Journal of Management and Strategic Business Leadership, 2026)
This study examines the use of Google Reviews as a source of patient satisfaction evaluation at RSUD Kota Tangerang using the SERVQUAL framework and Expectation-Disconfirmation Theory (EDT). The digitalization of healthcare services has encouraged patients to express their experiences through online review platforms, making Google Reviews an important source of real-time and organic feedback. However, studies analyzing online hospital reviews in Indonesian public hospitals remain limited. This research aimed to identify sentiment distribution across five SERVQUAL dimensions, analyze the relationship between service quality and patient satisfaction, and formulate strategic recommendations for hospital management. An explanatory sequential mixed-methods design was applied. A total of 204 Google Reviews from January 2023 to May 2026 were analyzed quantitatively using Spearman rank correlation (SPSS Version 26) after classification with a SERVQUAL-based codebook (κ=0.81; p<0.001). Qualitative data were obtained through in-depth interviews with eight hospital management informants and analyzed using thematic analysis. The findings showed an average rating of 3.38 (SD=1.87), with 57.8% positive and 40.7% negative sentiments. Reliability demonstrated the largest service quality gap (P−E=−2.356; 78.1% negative; ρ=−0.315; p<0.001) and the strongest negative correlation with ratings, while Empathy showed a significant positive relationship with patient satisfaction (ρ=0.153; p=0.029). Three of five SERVQUAL dimensions showed significant correlations with ratings. Interview results identified four main hierarchical barriers: values and motivation, organizational culture and leadership, human resources and demographics, and systems and infrastructure. The study concludes that Google Reviews can complement conventional patient satisfaction surveys and support hospital quality improvement strategies. Keywords: : Ewom; Expectation-Disconfirmation; Google Review; Mixed Methods; Patient Satisfaction; Public Hospital; SERVQUAL